Observation of linear magnetoelectric effect in a Dirac magnon antiferromagnet Cu3TeO6 - Shahee, Aga; Yoo, Kyongjun; Koteswararao, B.; Ter-Oganessian, N. V.; Kim, Kee Hoon (Frontiers in Materials, 2023)
Cu3TeO6, a three-dimensional antiferromagnet forming a unique spin-web lattice of spin-1/2 Cu2+ ions below the Néel temperature TN ≈ 62 K, has recently been found to exhibit topological Dirac or nodal magnon dispersion. In this study, we report the discovery of the linear magnetoelectric (ME) effects in Cu3TeO6 below TN. Our pyroelectric current measurements at a constant magnetic field (H) reveal a linear increase of electric polarization (P) with H for both P//H and P⊥ H configurations; a maximum P//[110] = 20 µC/m2 is obtained at µ0H//11¯0 = 14 T, corresponding to a linear ME coefficient 1.8 ps/m. Magnetic point group analysis and Monte-Carlo simulations confirm that finite linear ME coefficients are allowed in the off-diagonal and diagonal ME tensor components, consistent with the magnetic point group of 3¯′. As the parity-time symmetry can be broken in the presence of H or electric field E in the linear ME materials, we envisage that Cu3TeO6 should exhibit a H- or E-induced transformation in the topological magnon dispersion from a Dirac point/nodal line type into two Weyl point types.